The prevalence of hypertension, obesity and dyslipidemia in individuals of over 30 years of age belonging to minorities from the pasture area of Xinjiang - Luo Wen-Li; Yan Zhi-Tao; Wang Hong-Mei; Zu Feiya; Zhou Ling; Frommlet Florian; Yao Xiao-Guang; Hong Jing; Wang Xin-Ling; Li Nan-Fang (BMC, 2010)
Abstract Background The prevalence of population-wide hypertension, obesity and dyslipidemia has not been well studied in the pasture area of Xinjiang. The present epidemiological study was performed to determine the prevalence of hypertension, obesity and dyslipidemia in minority populations from the pasture area of Xinjiang and to discuss the potential risk factors for hypertension. Methods A population-based, cross-sectional study in the Xinjiang pasture area was performed which included 2251 participants aged over 30 years (90.33% participation rate) of whom 71.26% were Kazaks. Several risk factors were considered: hypertension (defined as systolic or diastolic blood pressure or both of at least 140/90 mmHg measured on one occasion or treatment for hypertension) overweight/obesity (body mass index ≥ 25 kg/m2) alcohol intake, smoking/tobacco use and dyslipidemia. Outcomes were prevalence of hypertension, obesity and dyslipidemia and the associated risk factors of hypertension detected by multivariate logistic regression analysis taking into account various metabolic and lifestyle characteristics. Results The prevalence of hypertension, overweight/obesity and dyslipidemia in all participants from the pasture area of Xinjiang was 51.9%, 47.9% and 49.2% respectively. Independently, the prevalence and awareness of hypertension was 52.6% and 15.3% among Kazaks (n = 1604), 54.6% and 14.1% among Uygurs (n = 418), 39.5% and 16.1% among Mongolians (n = 81) and 43.9% and 18.2% among non-Xinjiang-born Han immigrants (n = 148). The prevalence of overweight/obesity in Kazaks, Uygurs, Mongolians and Han immigrants was 46.7%, 48.9%, 62.5% and 50.3%, respectively. The prevalence of dyslipidemia in the four ethnic groups mentioned was 53.5%, 34.8%, 49.3% and 47.3%, respectively. The mean blood pressure in all participants was 136/86 mmHg (pre-hypertensive), the mean BMI was 24.7 kg/m2. Based on multiple logistic regression analysis, the significant risk factors for hypertension were age [1.07(1.06-1.09), P < 0.0001], overweight/obesity [overweight: 1.61(1.22-2.13), p = 0.0007; obesity: 1.95 (1.33-2.87), p = 0.0007], hypercholesterolemia [1.30(1.15-1.47), p < 0.0001] and an alcohol intake of over 30 g/day [2.22(1.43-3.45), p = 0.0004]. Conclusions The considerably high prevalence of hypertension, overweight/obesity and dyslipidemia among the minority population aged over 30 from the pasture area of Xinjiang calls for effective preventive measures. Age, increased body mass index, hypercholesterolemia and ≥30 g/d alcohol intake can be counted as risk factors for hypertension, but further genetic or environmental clarification would be desirable to explain the unusually high prevalence of the conditions mentioned above.